2020
DOI: 10.1002/app.49978
|View full text |Cite
|
Sign up to set email alerts
|

Nafion® reinforced with polyacrylonitrile/ZrO2 nanofibers for direct methanol fuel cell application

Abstract: Nafion ® membrane blended with polyacrylonitrile nanofibers decorated with ZrO 2 was successfully fabricated. The composite membrane showed improved proton conductivity, swelling ratio, thermal and mechanical stability, reduced methanol crossover, and enhanced fuel cell efficiency. The nanocomposite membranes achieved a reduced methanol crossover of 5.465 × 10 −8 cm 2 S −1 compared to 9.118 × 10 −7 cm 2 S −1 of recast Nafion ® membrane using a 5 M methanol solution at 80 C. The composite membrane also showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The alkaline stability of the membranes was determined by soaking the membrane in an alkaline solution then determining the IC every 24 h for 7 days. [30][31][32]…”
Section: Ion Conductivity and Alkaline Stabilitymentioning
confidence: 99%
“…The alkaline stability of the membranes was determined by soaking the membrane in an alkaline solution then determining the IC every 24 h for 7 days. [30][31][32]…”
Section: Ion Conductivity and Alkaline Stabilitymentioning
confidence: 99%
“…To demonstrate the use of polyacrylonitrile in Nafion, Sigwadi et al described a Nafion membrane reinforced with a blend of polyacrylonitrile (PAN) and zirconia oxide (ZrO 2 ) [ 68 ]. Due to the enhanced water uptake but the decreased swelling ratio in the presence of PAN, a higher proton conductivity was achieved in parallel with the lower methanol permeation, which contributes to the increase in selectivity ratio.…”
Section: Modification Strategiesmentioning
confidence: 99%
“…Considering that proton transfer in Nafion is still a challenge during high-temperature operation, it has been reported that the addition of hygroscopic inorganic oxides to Nafion can help maintain the relative humidity of the membrane, which can facilitate proton transport during fuel cell operation at high temperature [ 72 ]. Due to their high porosity, they are able to increase water retention in the membrane while also acting as Lewis acid sites to absorb more water [ 68 ]. Inorganic oxides also offer convincing mechanical properties to the membrane structure through the interaction between organic-inorganic components.…”
Section: Modification Strategiesmentioning
confidence: 99%
“…In the work of Msomi et al, Nafion-Polyacrylonitrile (PAN)/ZrO 2 nanofiber membrane samples were prepared using the recasting method and these membranes exhibited higher σ and also a better selectivity (σ/P M ). 5 In one of the latest studies of Kamarudin et al, the eggshell powder was used firstly as a calcium carbonate source to prepare Nafion/eggshell composite membrane. The composite membrane including 3% eggshell powder in weight had a proton conductivity of 0.24 S cm À1 and methanol permeability of 8.4 Â 10 À7 cm 2 s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…That is why many studies devoted to the growth of polymer‐based membranes with high methanol barrier properties and adequate proton conductivity using different approaches involving Nafion modification or new membrane designing. In the work of Msomi et al, Nafion‐Polyacrylonitrile (PAN)/ZrO 2 nanofiber membrane samples were prepared using the recasting method and these membranes exhibited higher σ and also a better selectivity ( σ / P M ) 5 . In one of the latest studies of Kamarudin et al, the eggshell powder was used firstly as a calcium carbonate source to prepare Nafion/eggshell composite membrane.…”
Section: Introductionmentioning
confidence: 99%